JAK1/3 inhibition preserves epidermal morphology in full‐thickness 3D skin models of atopic dermatitis and psoriasis. (1st January 2019) - Clarysse, K.; Pfaff, C.M.; Marquardt, Y.; Huth, L.; Kortekaas Krohn, I.; Kluwig, D.; Lüscher, B.; Gutermuth, J.; Baron, J.
Abstract: Background: Janus kinase (JAK) inhibition may be a promising new treatment modality for inflammatory (skin) diseases. However, little is known about direct effects of kinase inhibitors on keratinocyte differentiation and function as well as skin barrier formation. Objective: Our aim was to address the direct impact of kinase inhibition of the JAK1/3 pathways by tofacitinib on keratinocyte immune function and barrier formation in atopic dermatitis (AD) and psoriasis. Methods: 3D skin equivalents of both diseases were developed and concurrently pretreated with tofacitinib. To induce AD, 3D skin equivalents were stimulated with recombinant human IL‐4 and IL‐13. Psoriasis‐like conditions were induced by incubation with IL‐17A, IL‐22 and tumour necrosis factor α (TNFα). The activation of signal transducer and activator of transcription (STAT)1, STAT3 and STAT6 was assessed by Western blot analysis. Microarray analysis and quantitative real‐time PCR were used for gene expression analysis. Results: Tofacitinib pretreatment preserved epidermal morphology and reduced STAT3 and STAT6 phosphorylation of AD‐like and STAT3 phosphorylation of psoriasis‐like culture conditions in 3D skin models compared to sham‐controls. Filaggrin expression was fully maintained in the AD‐like models, but only partially in psoriasis‐like conditions after pretreatment with tofacitinib. In addition, tofacitinib upregulated DSC1, FLG and KRT1 . Using gene expression analysis, downregulation of POSTN and IL24 was observed in AD‐like conditions, whereas downregulation of IL20 and IL1B was observed in psoriasis‐like conditions. Conclusion: JAK1/3 inhibition counteracted cytokine‐induced AD‐ and psoriasis‐like epidermal morphology and enhanced keratinocyte differentiation in 3D skin models. This effect was more pronounced in the AD‐like models compared to the psoriasis‐like 3D skin models.